PELATIHAN PENGELOLAAN KEUANGAN BERBASIS EKONOMI BERKELANJUTAN PADA PENGELOLA BADAN USAHA MILIK DESA (BUMDES) DI KECAMATAN SIGALUH KABUPATEN BANJARNEGARA - Wita Ramadhanti; Triani Arofah; Oman Rusmana (Jurnal Pengabdian Bisnis dan Akuntansi Soedirman (JPBA), 2022)
Village-owned Enterprises was established in compliance with Indonesian Law Number 6/2014. Hence, since it is a top-down instructions, the development progress is not in a good condition. There are still so many of these institutions that having difficulty in managing their financial sustainability. Based on that, this community development will train the Village-owned enterprises’ manager how to managing entity’s sustainable economics. The training was held at June 8th, 2022 on Village-owned Enterprises’ managers from Sigaluh District, Banjarnegara County. There are 20 trainees as participants. The participants then given theoretical material and discuss the practical side of sustainability management, accounting, and tax. The attendees then asked to filling in pre-test and post-test that will be analysed statistically in order to check the successfulness of the workshop. The results shows that there are means differences between pre-test and post-test mark of the participants. It means that intervention from the community development team through theoretical material and practical discussions are success in developing Village-owned enterprises managers’ capacity for entities’ as well as villages’ economic sustainability